A multi-controllable selective fluorescent turn-on chemosensor for Al3+ and Zn2+ based on a new diarylethene with a 3-(4-methylphenyl)-1H-pyrazol-5-amine Schiff base group. Issue 43 (25th October 2018) - Gao, Wendan; Zhang, Yaping; Li, Hui; Pu, Shouzhi
Abstract: A novel diarylethene containing a 3-(4-methylphenyl)-1H-pyrazol-5-amine was synthesized. Its multi-responsive properties induced by UV/Vis lights and metal ions were studied in detail by absorption and fluorescence emission spectroscopy. It showed excellent fluorescence sensing ability for Al 3+ and Zn 2+ with very low detection limit. In addition, based on the multi-responsive characteristics, a logic circuit was constructed by using both UV/Vis lights and chemical species stimuli as inputs and fluorescence intensity as outputs. Moreover, the diarylethene was successfully applied to effectively detect Al 3+ and Zn 2+ in actual water samples. Graphical abstract: